PENGARUH PROFESIONALISME, KEPRIBADIAN HARDINESS, MOTIVASI DAN BUDAYA ORGANISASI PADA KINERJA AUDITOR DI KANTOR AKUNTAN PUBLIK - Temaja, I Putu Eka Arya Wedhana; Utama, I Made Karya (E-Jurnal Akuntansi; Vol 15 No 3 (2016), 2016)
This study aimed to examine the effect of professionalism, hardiness personality, motivation and organizational culture on the performance of auditors in the public accounting firm of Bali Province. The samples in this study using saturation sampling method. The data were collected using a survey method with questionnaire technique. Respondents in this study were 55 people. To test the quality of the data from the instruments used to do with the validity and reliability test. Test the classical assumption of normality test, multicollinearity and heteroscedasticity test, intended as a requirement to perform multiple linear regression tests. The results of multiple regression analysis showed that the variation of the variable performance of auditors can be explained by a variety of variables professionalism, hardiness personality, motivation and organizational culture by 82 percent. The results showed that professionalism, hardiness personality, motivation and organizational culture have a positive influence on the performance of auditors.
Keywords: professionalism; hardiness personality; motivation; organizational culture; performance auditor